The effects of mindfulness-based interventions on anxiety, depression, stress, and mindfulness in menopausal women: A systematic review and meta-analysis - Liu, Hongyang; Cai, Kexin; Wang, Jinyang; Zhang, Hailian (Frontiers in Public Health, 2023)
Background Mindfulness-based interventions (MBIs) are psychological interventions widely used in menopausal women. Currently, there is no evidence summary on the effectiveness of MBIs on anxiety, depression, stress, and mindfulness in menopausal women. This meta-analysis examines the effectiveness of MBIs in improving anxiety, depression, stress, and mindfulness scores in menopausal women. Methods A systematic search was conducted in PubMed, Embase, Web of Science, the Cochrane Library, CNKI (China National Knowledge Infrastructure), and Wanfang, using relevant terms such as MBIs as keywords and covering all studies published before March 13, 2022. The outcomes were anxiety, depression, stress, and mindfulness. The screening and extraction of data were conducted by two independent reviewers. Results A total of 1,138 menopausal women participated in 13 studies. Meta-analysis results showed that MBIs significantly reduced stress in menopausal women (SMD = −0.84, 95% CI: −1.64 to −0.05, p = 0.04), but no statistical differences were found in reducing anxiety (SMD = −0.40, 95% CI: −0.81 to 0.01, p = 0.06) and depression (SMD = −0.19, 95% CI: −0.45 to 0.07, p = 0.16) and in raising the scores of mindfulness (SMD = 0.37, 95% CI: −0.06 to 0.81, p = 0.09) in menopausal women. Conclusion MBIs may reduce stress in menopausal women, but their effect on improving anxiety, depression, and mindfulness needs further validation. Systematic review registration https://www.crd.york.ac.uk/prospero/#recordDetails.